ANALISIS SWOT SEBAGAI DASAR PERUMUSAN STRATEGI PEMASARAN USAHA AYAM PETELUR JANTAN PADA UD. JAYA ABADI DI DESA ROBYONG KECAMATAN PAKIS KABUPATEN MALANG - Khusnul Khotimah; Rois Arifin; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTAn Analysis of SWOT as the Basic Formulation of Marketing Strategy ofMale laying hens business at UD. Jaya Abadi in Robyong Village of Pakis ofMalang The research aimed at formulating the marketing strategy on the male laying hens business of UD. Jaya Abadi In Robyong Village of Pakis of Malang by using SWOT Analysis. SWOT analysis was used to find out the strengths, weaknesses, opportunities, and threats of UD. Jaya Abadi. The data collection used the technique of interview and documentation. The method used descriptive method with qualitative approach. The results of the SWOT analysis can be known that internal factors that become the main strength is the widest marketing area, the main weakness is the production capacity which has not been able to meet market demand. The external factors that become the main opportunity is the increasing demand, the main threat is the price fluctuations, both the price of DOC / chicks and chick prices. Based on the IE matrix, the the male laying hens business is in the IV squared. The marketing strategy that can be used by UD Jaya Abadi is a strategy of future integration, the strategy can be done by maintaining good relationship with the consumers, and the backward integration strategy can be done by strengthening the relationship with suppliers, the horizontal strategy can be done by increasing the supervision of competitors, and market development strategy can be done by increasing market share of the male laying hensKeywords: SWOT analysis, the marketing strategy